Managing sustainability in the hospitality and tourism industry: paradigms and directions for the future - Jauhari, Vinnie, Ed (Advances in hospitality and tourism book series, 2014)
This new book focuses on the important concern of sustainability in tourism and hospitality industry. As the world's natural resource base is limited, the world is looking for solutions in the domains of energy, water, alternate building materials, resource redeployment, and sustainable livelihoods as well. The tourism and hospitality industry is a large deployer of natural and created resources. Some of the themes the book addresses include:designing sustainable restaurantssustainable accommodation practicesdesigning green hotelsenergy c.